Representation of Love in Andrić’s Novel The Bridge on the Drina - Katušić, Bernarda (Poznańskie Studia Slawistyczne, 2015)
Starting with Erich Fromm’s thesis on love from his seminal work The Art of Loving (1956), the paper tries to show the way in which Fromm’s psycho-biological concept of love is represented differently in different historical formations in Andrić’s historical novel The Bridge on the Drina (1945). A brief analysis of the three love relations from Andrić’s novel reveals the process of the appearance of the concept of modern love, the moment in which love ceases to be a social instancje and becomes an individual act.